Athlete's Heart Assessed by Sit-Up Strength Exercises in Military Men and Women: The CHIEF Heart Study - Lin, Yu-Kai; Tsai, Kun-Zhe; Han, Chih-Lu; Lee, Jiunn-Tay; Lin, Gen-Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Greater changes in cardiac structure and function in response to physical training have been observed in male athletes than in female athletes as compared with their sedentary controls. However, there were rare studies for the sex-specific cardiac remodeling related to strength exercises in Asian athletes. Methods: This study included 580 men and 79 women, averaged 25 years of age, for a 6-month military training program in Taiwan. Both men and women attended a 2-minute sit-up test to assess muscular strength after the training. The test performance falling one standard deviation above the mean (16%) was to define the superior eliteness of athletes. Cardiac structure and function were investigated by electrocardiography and echocardiography for men and women. Multiple logistic regression was used to determine the predictors of elite athlete status. Results: In men, greater QTc interval, left ventricular mass adjusted to body surface area (LVMI), lateral mitral E’/A’ ratio and right ventricular systolic pressure, and lower diastolic blood pressure were independent predictors of elite strength athletes in the sit-up test [odds ratio (OR) and 95% confidence intervals: 1.01 (1.00, 1.02), 1.02 (1.00, 1.04), 1.45 (1.06, 1.98), 1.13 (1.06, 1.23) and 0.96 (0.93, 0.99), respectively]. In contrast, in women, greater right ventricular outflow tract dimension was the only independent predictor of elite strength athletes in the sit-up test [OR: 1.26 (1.04, 1.53)]. Conclusions: In the 2-minute sit-up test, cardiac characteristics differ between elite male and female athletes. While greater QTc interval, LVMI and diastolic function of left ventricle predict the eliteness of male strength athletes, greater right ventricular chamber size characterize elite female strength athletes.